Issues in applying SLA : theories toward reflective and effective teaching - Zeraatpishe, Mitra; Faravani, Akram; Kargozari, Hamid Reza; Azarnoosh, Maryam (Critical new literacies : the praxis of English language teaching and learning (PELT), 2018)
"A reflective teacher as a growth-minded person seeks opportunities to continue professional development. Reflection not only ignites a teacher's desire for improvement, but also inspires continuous learning. Through accurate grasp of self-assessment, confidence, self-appraisal, a reflective practitioner can plant the seeds of effective teaching. This book aims to guide EFL teachers to teach language reflectively and effectively. It includes two parts, the first focuses on the SLA theories and their impact on language teaching and the second centers on the reflective and effective teaching of language components and skills. The editors hope this book could contribute to those who wish to become effective teachers since this results in nurturing learners' cravings to learn in a safe and supportive environment"--